Peran Kebijakan Dana Desa dalam Memberdayakan Masyarakat di Desa Tanah Abang Selatan - Umi Purwanti; Suandi Suandi (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2022)
This study aims to determine how the role of village funds in community empowerment and the efforts made by the village government in improving community empowerment. The research method uses descriptive qualitative research with data collection methods free guided interviews, observation and documentation. The results of the study indicate that the empowerment of the people of Tanah Abang Selatan Village before the existence of village funds has not been able to be felt by the community as a whole. However, after the Village fund, the community began to feel a positive impact. The village government has also made efforts to increase community empowerment. Community participation increased after the Village fund program in community development and empowerment. The conclusion of the study shows that the role of the village government in improving community empowerment is good and has a positive impact through village funds in community empowerment. Keywords: Community Empowerment, Role, Village Fund.